AB0552 Analysis of patients lost to follow-up in an outpatient rheumatology clinic. (23rd January 2014) - Solmaz, D.; Cetin, P.; Erenci, S.; Sari, I.; Birlik, M.; Akar, S.; Onen, F.; Akkoc, N.
Abstract : Background: Ankylosing Spondylitis (AS) patients in routine clinical practice are usually seen at regular intervals (every few weeks to months) depending on their disease activity and type of therapy. However, many patients do not attend the clinic within the recommended time frame. It is not known how these patients lost to follow-up compare to those who are regular clinic attenders, as well as the reasons for their nonattendance. Objectives: We aimed primarily to assess the AS patients lost to follow-up in our center and compare them with the regularly followed patients, particularly in regard to disease activity, physical functioning and health related quality of life. We also sought to identify the reasons for loss to follow-up. Methods: Using hospital records, we identified 514 AS patients (383 M; 44 ± 12.0) who were admitted to the clinic at least one year prior to this study. Loss to follow-up was defined as clinic non-attendance for one or more years. For a fair comparison of groups, we excluded patients on biologic therapy (n=149). Non-attending patients were contacted by phone and were invited to return for review. The patients, who did not accept to attend, were interviewed by phone. Full clinical assessment was made on the patients who attended the clinic, including disease activity (BASDAI, ASDAS CRP), functional (BASFI, HAQ), quality of life (ASQOL) and mobility (BASMI) measures. The corresponding data for the regularly followed patients were obtained from their last visit. Comparisons of categorical data between groups were made using the chi-square test. The Mann-Whitney U test was used to analyze independent data. Wilcoxon test was used to analyze related data. Results: From a total of 167 patients (124 M;46 ±12) lost to follow-up, 43 (31 M; 46 ± 11.3) could not be reached after a minimum of 2 phone call attempts; 65 (47 M; 47 ± 13.6) were interviewed by telephone and 59 patients (46 M; 44 ± 10.6) were assessed at the clinic. The reasons for non-attendance were good symptomatic status (72%), changing physicians (16.1%), moving to another location (6.8%) and health insurance problems (5.1%). Average duration lost to follow-up was 1.7±0.8 years. There were no differences between the patients who were lost to follow-up and those who were regular clinic attenders, in respect to age and sex distribution, treatment, ASDAS CRP, BASMI, ASQOL, HAQ, CRP and ESR (Table ). Patients lost to follow-up had lower mean BASDAI score at baseline and lower mean BASFI score at last visit. Conclusions: In this one center study, AS patients lost to follow-up, in general are quite similar to those who were regularly followed. Lower BASDAI and BASFI scores at baseline and at last visit respectively may suggest that the non-attending AS patients may have a milder disease course. Strategies should be developed to increase the attendance rate of this group of patients. Disclosure of Interest: None Declared